Community Development and Social Regeneration: How the Third Sector Addresses the Needs of BME Communities in Post-Industrial Cities - Wallace, James A. 1944-; Cornelius, Nelarine (2010)
Interest in third sector organisations (TSOs) is growing as their role in addressing social regeneration, especially in urban environments, is regarded as crucial by governmental and supra-governmental organisations. The challenge is increased in multicultural environments, where those from ethnic minorities may struggle to participate in the mainstream economy and society more broadly. There is an assumption that TSOs make a positive contribution to the social good of the diverse communities and client groups that they serve. However, although there have been many studies of ethicality in commercial and public sector organisations, few focus on TSOs. Furthermore, black and minority ethnic (BME) TSOs, in particular face specific pressures, caught between the high expectations of their capacity to engage with diverse communities where the public sector has failed and, in common with all TSOs, the struggle to secure the resources necessary to manage their organisations and deliver front-line services. In this article, we investigate how implicitly ethicality is constructed in TSOs, including those with a primary mission to provide support for and services to BME communities. Building on information obtained for 305 TSOs in a post-industrial city we develop a structural equation model (SEM) in order to evaluate the relationships between elements that we argue comprise ethicality. We then assess the manner in which TSOs generally, and BME TSOs specifically, vary in the manner in which they communicate their ethical purpose and the outcomes of their actions.
Keywords: Ethicality; Structural equation modelling; Capabilities Approach; Black and minority ethnic (BME); Third sector organisations